PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MD CELL SAMARINDA - Marten Apuy; Suarno; Keshia Putri Couwindra (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2025)
The Influence of Leadership and Compensation on Employee Performance of MD Cell Samarinda (Under the guidance of Benediktus Sunarsi and Sudirman). The study is to determine whether